2013
DOI: 10.1186/1471-2202-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Differential neuronal expression of receptor interacting protein 3 in rat retina: involvement in ischemic stress response

Abstract: BackgroundReceptor-interacting protein 3 (RIP3), a member of RIP family proteins, has been shown to participate in programmed necrosis or necroptosis in cell biology studies. Evidence suggests that necroptosis may be a mode of neuronal death in the retina.ResultsIn the present study we determined the expression of RIP3 in normal rat retina and its changes following acute high intraocular pressure (aHIOP). RIP3 immunoreactivity (IR) was largely present in the inner retinal layers, localized to subsets of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…Our data suggest that the Ripk1 and Ripk3 proteins, which are required to initiate necroptosis (Degterev and Yuan, 2008; Galluzzi and Kroemer, 2008; Takahashi et al, 2012; Vandenabeele et al, 2010), are present in control and ischemic RGCs. It should be noted that the pattern of Ripk3 protein distribution in sham-operated and IR mouse retinas coincides with Ripk3 protein distribution in sham-operated and ischemic rat retinas (Huang et al, 2013). We found that inhibiting the activation of the Ripk1/Ripk3-pathway in RGCs, using Nec1, significantly reduced IR-induced retinal damage.…”
Section: Discussionmentioning
confidence: 71%
“…Our data suggest that the Ripk1 and Ripk3 proteins, which are required to initiate necroptosis (Degterev and Yuan, 2008; Galluzzi and Kroemer, 2008; Takahashi et al, 2012; Vandenabeele et al, 2010), are present in control and ischemic RGCs. It should be noted that the pattern of Ripk3 protein distribution in sham-operated and IR mouse retinas coincides with Ripk3 protein distribution in sham-operated and ischemic rat retinas (Huang et al, 2013). We found that inhibiting the activation of the Ripk1/Ripk3-pathway in RGCs, using Nec1, significantly reduced IR-induced retinal damage.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have reported that RIP-3 expression is rapidly increased in cells of the GCL and INL in the rat retina following acute increases in intraocular pressure (IOP). 54 It was also reported that RIP-3 immunolabeling was colocalized with the PI-positive cells in the GCL that indicates the involvement of RIP-3 in necroptotic cell death. Our western blotting analysis showed a significant increase in RIP-3 protein expression following I/R, which was significantly reduced in A2-deficient retinas.…”
Section: Discussionmentioning
confidence: 89%
“…174,175 In one study, the death-associated protein DAXX was suggested to be a critical downstream target of RIPK3, 175 although this has not been confirmed in this or any other system. 174,175 In one study, the death-associated protein DAXX was suggested to be a critical downstream target of RIPK3, 175 although this has not been confirmed in this or any other system.…”
Section: Ophthalmology and Necroptosismentioning
confidence: 95%